Self-segregation of myelin membrane lipids in model membranes - Yurlova, Larisa; Kahya, Nicoletta; Aggarwal, Shweta; Kaiser, Hermann-Josef; Chiantia, Salvatore; Bakhti, Mostafa; Pewzner-Jung, Yael; Ben-David, Oshrit; Futerman, Anthony H.; Brügger, Britta; Simons, Mikael (Biophysical journal, 2011)
Rapid conduction of nerve impulses requires coating of axons by myelin sheaths, which are multilamellar, lipid-rich membranes produced by oligodendrocytes in the central nervous system. To act as an insulator, myelin has to form a stable and firm membrane structure. In this study, we have analyzed the biophysical properties of myelin membranes prepared from wild-type mice and from mouse mutants that are unable to form stable myelin. Using C-Laurdan and fluorescence correlation spectroscopy, we find that lipids are tightly organized and highly ordered in myelin isolated from wild-type mice, but not from shiverer and ceramide synthase 2 null mice. Furthermore, only myelin lipids from wild-type mice laterally segregate into physically distinct lipid phases in giant unilamellar vesicles in a process that requires very long chain glycosphingolipids. Taken together, our findings suggest that oligodendrocytes exploit the potential of lipids to self-segregate to generate a highly ordered membrane for electrical insulation of axons.